Video streaming performance at FTMM, KUiTTHO - Aman, Hannani
The distribution of digitized video data, whether on-demand or streaming, is rising tremendously among Internet users in Malaysia especially in areas such as education, communication and television broadcasting. Based on this progression, a research has been conducted to study the relationship between network performance and the quality of video data streamed in FTMM, KUiTTHO local area network. Different types of content and category of video data are streamed to the network which is equipped with LAN 100Base T technology. To achieve the objective, experimental approach is applied to different types of video content namely lecture clips, movie clips and music clips. The quality of transmitted video data is very much depended on two main factors which are packet delay and packet loss. Based on the experiment that has been conducted, packet delay is caused by network traffic condition, video content, LAN architecture, hardware and transmission medium used. In addition to this, the experiment also has shown that packet loss is caused by data burst. This situation happened when packet queue is overloading the router. This research confirms that video streaming quality can be upgraded with the use of better communication medium such as fiber optic, the exploitation of up-to-date network hardware, the utilization of bigger capacity hard disk and finally with the use of smaller window scale in displaying the video content.